Smallwood Interview 09B - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
In this interview with Robert Pitt, Joseph (Joey) Smallwood describes how he decided to join the liberal movement in the 1920's; he came to believe that the Liberal Party was the party of the working man. Smallwood had worked in union organizing in the Corner Brook area, and worked to convince Richard Squires that he could win that riding for the Liberal Party. Speaks about campaigning with Sir Richard Squires and about political campaigns in general, and what he has learned from these experiences.